Breadth and Duration of Meningococcal Serum Bactericidal Activity in Health Care Workers and Microbiologists Immunized with the MenB-FHbp Vaccine - Lujan, Eduardo (Clin Vaccine Immunol, 2017)
MenB-FHbp is a meningococcal serogroup B vaccine with two factor H binding protein (FHbp) antigens from subfamilies A and B. For licensure, efficacy was inferred from serum bactericidal antibody (SBA) responses to four reference strains. Only limited information is available on the breadth or duration of protective SBA responses to genetically diverse disease-causing strains. Seventeen health care or laboratory workers were immunized with two (n = 2) or three (n = 15) doses of MenB-FHbp at 0, 2, and 6 months. SBA levels were measured against 14 serogroup B case isolates, including 6 from U.S. college outbreaks and 2 from Quebec during hyperendemic disease. Compared with preimmunization titers, the proportion of subjects with ≥4-fold increases in SBA titer 1 month after 2 doses of vaccine ranged from 35% to 94% for six isolates with FHbp subfamily A and from 24% to 76% for eight isolates with subfamily B FHbp. The respective proportions with ≥4-fold titer increases at 1 month after dose 3 were 73% to 100% and 67% to 100%. At that time point, the proportion of subjects with titers of ≥1:4 (presumed sufficient for short-term protection) ranged from 93% to 100% for all 14 isolates. By 9 to 11 months after dose 3, 50% or fewer of the subjects with follow-up sera had protective titers of ≥1:4 for 4 of 9 isolates tested. Three doses of MenB-FHbp elicited short-term protective SBA responses to diverse disease-causing serogroup B strains. For some strains, serum titers declined to <1:4 by 9 to 11 months, which raises concerns about the duration of broad, long-term protection. (This study has been registered at ClinicalTrials.gov under registration no. NCT02569632.)